Growing Up Amid Ethno‐Political Conflict: Aggression and Emotional Desensitization Promote Hostility to Ethnic Outgroups. Issue 5 (September 2016) - Niwa, Erika Y.; Boxer, Paul; Dubow, Eric; Huesmann, L. R.; Shikaki, Khalil; Landau, Simha; Gvirsman, Shira D.
Abstract : Ethno‐political violence impacts thousands of youth and is associated with numerous negative outcomes. Yet little research examines adaptation to ethno‐political violence over time or across multiple outcomes simultaneously. This study examines longitudinal patterns of aggressive behavior and emotional distress as they co‐occur among Palestinian ( n  =   600) youth exposed to ethno‐political violence over 3 years in three age cohorts (starting ages: 8, 11, and 14). Findings indicate distinct profiles of aggressive behavior and emotional distress, and unique joint patterns. Furthermore, youth among key joint profiles (e.g., high aggression–emotional desensitization) are more likely to endorse normative beliefs about aggression toward ethnic outgroups. This study offers a dynamic perspective on emotional and behavioral adaptation to ethno‐political violence and the implications of those processes.